CAPRIN2 upregulation by LINC00941 promotes nasopharyngeal carcinoma ferroptosis resistance and metastatic colonization through HMGCR - Qiu, Lin; Zhou, Rui; Zhou, Ling; Yang, Shiping; Wu, Jiangxue (Frontiers in Oncology, 2022)
Distant metastasis is the main cause of death in nasopharyngeal carcinoma (NPC) patients. There is an urgent need to reveal the underlying mechanism of NPC metastasis and identify novel therapeutic targets. The ferroptosis resistance and survival ability of extracellular matrix (ECM)-detached tumor cells are important factors in determining the success of distant metastasis. In this study, we found that CAPRIN2 contributes to the ferroptosis resistance and survival of ECM-detached NPC cells. Moreover, CAPRIN2 serves as a positive regulator of NPC cell migration and invasion. HMGCR, the key metabolic enzyme of the mevalonate pathway, was identified as the key downstream molecule of CAPRIN2, which mediates its regulation of ferroptosis, survival, migration and invasion of NPC cells. Lung colonization experiments showed that downregulation of the CAPRIN2/HMGCR axis resulted in reduced lung metastasis of NPC cells. Erastin treatment inhibited the ability of NPC cells to colonize the lungs, which was further enhanced by CAPRIN2/HMGCR axis downregulation. Regulated by upstream LINC00941, CAPRIN2 is abnormally activated in NPC, and its high expression is associated with a poor prognosis. In conclusion, CAPRIN2 is a molecular marker of a poor prognosis in NPC, and the LINC00941/CAPRIN2/HMGCR axis provides a new target for the treatment of NPC metastasis and ferroptosis resistance.